Daily dynamics of blood transaminase under normal light conditions and modified under the influence of alcoholic beverages - Tamara Ismailovna Dzhandarova; Svetlana Sergeevna Shabanova (Наука. Инновации. Технологии)
A study of daily dynamics of transaminases in the blood under the influence of alcoholic beverages in rats. It was found that the treated rats as alcohol and non-alcoholic beer, the daily dynamics of the content and alanine aminotransferase, aspartate aminotransferase and disorganized even at ordinary light mode and is particularly aggravated during shift illumination mode. These animals mounted significantly higher values aspartate levels in the blood for days, compared with data for control animals throughout the experiment.